“Rooms of Temporary Solitude” as Element of Safe and Comfort Educational Environment - I. S. Samokhin; M. G. Sergeyeva; N. L. Sokolova; N. Y. Bezrukova (Научный диалог, 2018)
The article considers the prospects of using the innovation proposed by the authors to improve the level of safety and comfort of the school educational environment. The relevance of the study is due to the law “On Education in the Russian Federation,” aimed at further humanization of the educational process. The characteristics of the author’s project - “rooms of temporary solitude,” which are designed as locked from the inside single cabins with a chair and a pull-out table, where any student can retire during the break. It is noted that these rooms should not be confused with the so-called “sensory rooms” (or “relaxation rooms”), which perform more functions and do not require the presence of only one person. In the practical part, the results of a written survey of students in grades 7-9 are analyzed, allowing to see the needs of students in solitude between the lessons and their attitude to the proposed innovation. It is shown that “temporary privacy rooms” in Russian schools is supported by more than half of the test participants - 53.3 %. The share of respondents seeking or at least inclined to visit such booths is 46.4 %. The reasons why students want to make a change alone are given.